Cause‐specific mortality rates in patients with diabetes according to comorbid macro‐ and microvascular complications: BioBank Japan Cohort. Issue 1 (27th August 2020) - Yokomichi, Hiroshi; Nagai, Akiko; Hirata, Makoto; Mochizuki, Mie; Kojima, Reiji; Yamagata, Zentaro; ,
Abstract: Objective: This study aimed to compare cause‐specific mortality rates in patients with type 2 diabetes with and without various vascular complications. Methods: In Japanese hospitals, we followed up 30 834 patients with a mean age of 64.4 (standard deviation [SD]: 11.1) years. Patients were followed up from 2003 to 2007 for a median of 7.5 (interquartile range: 6.1‐9.7) years. We calculated cause‐specific mortality rates (number of deaths/1000 person‐years) and confounder‐adjusted hazard ratios in patients with macrovascular disease and in those with diabetic nephropathy, neuropathy and retinopathy, allowing for overlap of complications. Results: All‐cause mortality rate was highest (51.4) in the nephropathy group, followed by the macrovascular disease group (45.2), the neuropathy group (39.5), the retinopathy group (38.7) and the nonvascular complication group (18.1). In the nephropathy group, morality rates of ischaemic heart, cerebrovascular, and infectious diseases and cancer were also highest among the groups. However, the cancer mortality rate was similar among the vascular complication groups. Relative to the nonvascular complication group, covariate‐adjusted hazard ratios for ischaemic heart and cerebrovascular disease mortality were triple to quadruple in the macro‐ and microvascular complication groups. All‐cause mortality rates rose exponentially according to age. Conclusion: Highest risks of all‐cause, cancer, and ischaemic heart, infectious, and cerebrovascular disease mortality were determined in Japanese patients with diabetic nephropathy. Although cancer is the primary cause of death in Japanese patients with diabetes, cancer mortality rates are similar among those with and without vascular complications. Abstract : Patients with diabetic nephropathy have the highest mortality rates of all causes, cancer, and macrovascular and infectious diseases. The primary cause of death of patients with diabetes with and without all vascular complications was cancer. The cancer mortality rate was similar, regardless of whether vascular complications were present.